Analysis of Alienative Commitment and Transformational Leadership on Employee Performance by Moderating Political Skills at the Jakarta Special Regional Election Supervisory Agency - Ari Soeti Yani; Ahmad Komarul Anam (Journal of Business and Behavioural Entrepreneurship, 2024)
The impact of alienative commitment and transformational leadership on employee performance with the moderating variable political skill. 67 respondents aged between 20 and 40 years participated in this research. The sample of respondents used to collect data was via a g-form distributed via WhatsApp. The method used to manage data uses Partial Least Squares software to test hypotheses. The results obtained show that alienative commitment has an impact on employee performance, transformational leadership has an impact on employee performance, and political skills can moderate the impact of alienative commitment on employee performance, and political skills can moderate the impact of transformational leadership on employee performance.  In this research it was found that if you want to improve employee performance, you need to have good commitment and transformational leadership, and good political skills will motivate you to do so.